2015
DOI: 10.1016/j.cell.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Induced Blood Vessels Guide Schwann Cell-Mediated Regeneration of Peripheral Nerves

Abstract: SummaryThe peripheral nervous system has remarkable regenerative capacities in that it can repair a fully cut nerve. This requires Schwann cells to migrate collectively to guide regrowing axons across a ‘bridge’ of new tissue, which forms to reconnect a severed nerve. Here we show that blood vessels direct the migrating cords of Schwann cells. This multicellular process is initiated by hypoxia, selectively sensed by macrophages within the bridge, which via VEGF-A secretion induce a polarized vasculature that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
724
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(746 citation statements)
references
References 43 publications
17
724
3
2
Order By: Relevance
“…For example, hypoxia upregulates VEGF production after nerve injury, initiating migration of Schwann cells 18 . VEGF also stimulates formation of endoneurial blood vessels into hypoxic areas, directing Schwann cells to bridge the gap between the proximal and distal nerve stumps 18 .…”
Section: Schwann Cells and Their Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hypoxia upregulates VEGF production after nerve injury, initiating migration of Schwann cells 18 . VEGF also stimulates formation of endoneurial blood vessels into hypoxic areas, directing Schwann cells to bridge the gap between the proximal and distal nerve stumps 18 .…”
Section: Schwann Cells and Their Interactionsmentioning
confidence: 99%
“…For example, hypoxia upregulates VEGF production after nerve injury, initiating migration of Schwann cells 18 . VEGF also stimulates formation of endoneurial blood vessels into hypoxic areas, directing Schwann cells to bridge the gap between the proximal and distal nerve stumps 18 . However, studies have shown that diabetes reduces expression of the Schwann-cell-derived neurotrophic factors ciliary neuronotrophic factor (CNTF) 19 and sonic hedgehog 20 , which act on neurons and endothelial cells, respectively.…”
Section: Schwann Cells and Their Interactionsmentioning
confidence: 99%
“…Hallmarks of Wallerian degeneration are as follows: (a) detachment of resident Schwann cells from associated axons, (b) transition of these Schwann cells into a “repair Schwann cell” phenotype, (c) breakdown of the blood–nerve barrier, and (d) influx of macrophages into the tissue that, (e) in concert with “repair Schwann cells,” phagocytize axonal and myelin‐derived debris (Chen, Yu, & Strickland, 2007; Jessen, Mirsky, & Lloyd, 2015). During the regeneration phase, macrophages support “repair Schwann cells” in mediating axonal regrowth to re‐innervate the target tissue (Cattin et al, 2015; Mietto, Mostacada, & Martinez, 2015; Mokarram, Merchant, Mukhatyar, Patel, & Bellamkonda, 2012). Regeneration is completed when inflammatory processes resolve and “repair Schwann cells” redifferentiate.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that such space is quickly filled with plasma exudate composed mostly of a fibrin network and platelets. It has been recently shown that blood vessel formation and polarized growth precedes Schwann cell migration, which in turn produce the so-called Bands of Büngner (Cattin et al, 2015). Such cell cords guide the growing axons toward the distal stump of the nerve.…”
Section: Ratio Of the Massesmentioning
confidence: 99%